Best Digital Platforms in ELT during New Norms Era for Remote Area - Benni Satria (Universitas Maritim Raja Ali Haji, 2021)
The use of E- learning in English Language Teaching (ELT) has been strongly promoted since the pandemics Covid-19 is widely spread. Many researches have been conducted to find the best digital online learning to be used in the classroom. However, little to no research investigates about the most suitable digital online learning for the students living in the remote area whereas, especially in Indonesia, there were so many remote areas. Thus, this paper assists to describe the best digital platforms to be used in the remote Area. There were 15 ELT students involved as the participants. The chosen students were the students living in remote area. The instruments were a questionnaire. The result showed that Messenger Application, especially WhatsApp is the most preferred by the students living in the remote area, following by LMS represented by google classroom, and the last is video conference, particularly zoom. The finding of this research can become a consideration for the educators, especially teaching in remote area, in selecting the digital platform in online learning.